Kontroversi Pemanfaatan Gadai Sawah oleh Murtahin Berdasarkan Prinsip Mazhab Imam Syafi’i - Wardani, Besse (Fawaid : Sharia Economic Law Review, 2024)
The study aims to describe and identify the practice of utilizing rice field pawn objects and then analyze Imam Syafi'i's views on the utilization of rice field pawn objects. This study uses a qualitative method with a normative empirical research type, field research with data collection through observation, interviews and documentation. Based on the results of this study, it shows that the practice of rice field pawn in North Tongauna District, Konawe Regency uses two forms, namely utilization by rahin with a profit-sharing system and utilization by murtahin, a system of utilizing pawned rice fields during the pawn period and the results of the rice fields are taken entirely by the murtahin. The practice of pawning rice fields with this system is not entirely in accordance with the opinion of Imam Syafi'i who does not allow murtahin to utilize pawned goods, but Imam Syafi'i does not prohibit it absolutely because murtahin is allowed to utilize pawned goods when the requirements for such utilization are not carried out in the contract, but if the contract mentions the requirements for utilization by murtahin, then that is not permitted by Imam Syafi'i. Even though the local community in the concept of worship uses the Imam Syafi'i school of thought, not all people use the Imam Syafi'i school of thought in muamalah. Placing a pawn should be based on a sense of mutual help, but if it is based on wanting to make a profit then it is better to use a rental contract, so that there is no debate about the permissibility of using the item. Kata Kunci: Sawah, Objek Gadai, Murtahin, Imam Syafi'i